The Effects of Trade Exposure on Marriage and Fertility Choices: Evidence from Brazil - Breno Braga (Institute of Labor Economics (IZA), 2018)
This paper investigates the effect of a large economic shock on marriage and fertility choices. I exploit the 1990's trade liberalization in Brazil, which created exogenous negative labor market shocks to regions most exposed to foreign competition. While trade liberalization had a positive impact on reducing the price of consumer goods in Brazil, it also negatively impacted employment in previously protected industries, affecting men more than women. I find that young women living in regions more exposed to international competition are less likely to have children. Most effects persist for 20 years after trade liberalization. I use causal mediation analysis to show that declines in the employment rate of young men is an important driver of changes in fertility outcomes of young women. Changes in women's employment opportunities are not a mediator for the effect of trade exposure on fertility. There is no evidence of changes in marriage rates across regions exposed to trade liberalization.
Keywords: F16; J12; J13; J21; J23; 330; marriage rates; fertility; trade liberalization